HUBUNGAN ANTARA HARGA DIRI TERHADAP PENGUNGKAPAN DIRI DALAM PENGGUNAAN MEDIA SOSIAL PADA REMAJA - Erawati, Ni Putu Widya; Devi, Ni Luh Putu Shinta; Puspita, Luh Mira (Coping: Community of Publishing in Nursing, 2021)
The developmental task that must be achieved as a result of changes in adolescents is the search for identity. This search for self-identity will affect various aspects of adolescents, one of which is self-disclosure. In the age of technology, teenagers use social media more as a means to reveal information about themselves. Self-disclosure in the use of social media is influenced by various factors, one of which is self-esteem. The purpose of this study was to determine the relationship between self-esteem and self-disclosure in the use of social media in adolescents at SMP Negeri 2 Tabanan. This study used descriptive - correlative with a cross sectional approach. In this study, the sample was taken using cluster random sampling technique. The sample size used was 348 students. The conclusion of the analysis using the Spearman Rank test shows that there was no significant relationship between self-esteem and self-disclosure in the use of social media in adolescents with p value = 0.180 (? = 0.05). Suggestions from researchers to students to be more careful and wise in using social media and not to fake identities or provide information that is not in accordance with reality